Real-Time-PCR Assay Based on Phosphoglycerate Kinase Gene for Detection of Entamoeba histolytica Trophozoites in Stool Samples in Holy Karbala, Iraq (Medico Legal Update, 2021)
Amebiasis is an important cause of diarrheal disease worldwide and has been associated with childhoodmalnutrition. E.histolytica diagnosed usually by microscope, which consider as traditional diagnosis andare neither sensitive nor specific detection of Entamoeba histolytica(1). Real-time PCR assay developed forsensitive and specific detection of the intestinal Protozoan parasites Entamoeba histolytica directly fromhuman feces(2). The RT-PCR assay was able to detect as little as 0.1 parasite per g of feces(3). The currentstudy based on Phosphoglycerate kinase gene (PGK) is a major enzyme used in glycolysis, in the first ATPgenerating step of the glycolytic pathway so the PGK is an enzyme that catalyzes the reversible transfer ofa phosphate group from 1,3-bisphosphoglycerate (1,3-BPG) to ADP producing 3-phosphoglycerate (3-PG)and ATP(4). In our study, depend on PGK as target for Real time PCR assay for detection the trophozoitestage of E.histolytica in stool samples of infected persons.In the current study, a total of 300 human fecal samples were collected from children (less than one year-15year) that suspected to infection with amoebiasis which admitted to hospitals and primary care centers in thecity center, Al-Hindiya district and Nahiat Al -Hurr (100 samples from each region) during the period fromFebruary 2019 to January 2020. Fecal samples processed by direct wet smear and formalin ethyl acetateconcentration method followed by iodine staining and was microscopically examined for E.histolytica.Microscopically positive samples were then subject to Real-time PCR. This is the first study in Iraq using thePhosphoglyceratekinase gene as target for molecular techniques to determine the presence of E. histolyticatrophozoites.in stool samples.